Poverty Reduction and Growth Trust-Review of the Interest Rate Structure-Postponement. (Policy Papers; Policy Paper ;, 2019)
This paper proposes to postpone the deadline for the next interest rate review by six months in light of the timing of the second stage of the Low-Income Countries (LIC) Facilities Review, and to maintain the zero percent interest rates applicable to ECF, SCF and ESF balances for this period.